Influence of Dopant Concentration and Steric Bulk on Interlayer Diffusion in OLEDs. Issue 1 (25th October 2017) - McEwan, Jake A.; Clulow, Andrew J.; Nelson, Andrew; Wang, Renjie; Burn, Paul L.; Gentle, Ian R.
Abstract: The performance of organic light‐emitting diodes (OLEDs) can change when they are subjected to thermal stress after manufacture. The effect of heat on OLED film stacks is studied, in which the emissive layer (EML) comprises either a phosphorescent iridium(III) dopant blended in a host at different concentrations or materials with alkyl substituents to increase the steric bulk of the host and/or dopant. Neutron reflectometry with in situ photoluminescence measurements shows that interdiffusion between the emissive and hole transport layers within the films occurs on thermal annealing. Interdiffusion occurs independent of dopant concentration or steric bulk of the EML components. Importantly, when held at relatively low temperatures, the EML materials are found to only partially diffuse into an adjacent charge transport layer. The movement of materials is found to correlate with the change in luminescence from the hole transport material and an initial enhancement of the emission from the iridium(III) dopant. The results provide an explanation for the burn‐in often observed for OLEDs as well as the need to change the driving characteristics over time to ensure that pixels can be held at the requisite brightness. Abstract : Neutron reflectometry with in situ photoluminescence measurements shows that interdiffusion between organic light‐emitting diode (OLED) emissive and hole transport layers occurs on thermal annealing. Interdiffusion occurs independent of dopant concentration or steric bulk of the emissive layer components and is correlated with the change in film luminescence. The results provide an explanation for the burn‐in often observed for OLEDs.